"Hero of Our Time in Modern Prose" (Филологический класс, 2009)
The article is devoted to problems of modern literature, in particular to the attention of the writers of the end of 20 - the beginning of the 21st century to heroes of the classics. Noting intertextuality of works, the author analyzes the images of heroes in modern literature (on the material of the novels of V. Makanin`s the Underground, or the Hero of our time or Generation "P", of V. Pelevin`s the Spiritless: the story of a small man") and makes a conclusion about the dynamics of the image of a hero: from the seeking himself " internal exile" in the elder generation of writers to the appearance of the young "hero of time", for whom the cynicism and lack of mercy turns into a norm of life.